A hermenêutica filosófica como filosofia : uma crítica interna ao pensamento de Gadamer - Reis, Mauricio Martins (2015)
This research is in charge of responding whether philosophical hermeneutics, which became autonomous within the framework of the thought of Hans-Georg Gadamer the claim of universality of the hermeneutical problem attribute, may be qualified as genuine philosophy. The underlying theme of the thesis covers the main features of Gadamer's philosophical hermeneutics in order to promote a kind of internal criticism about its corresponding assumptions, especially those that revolve around the universal primacy of the historicity of understanding. It advocates the need to counteract against the transcendental horizon of meaning, significantly accentuated by philosophical hermeneutics through the incidence of historical understanding that runs through each interpretation about the world, the transcendental horizon of normative validity, responsible for critical and reflective bypass any thought that title itself as legitimately philosophical. In these terms, hermeneutics as philosophy, to achieve the desired universality platform, must claim at the same time the substrate of normative rationality validation, so as not to incur into a kind of ontological hypertrophy, acting just like a redundant substitute hermeneutics of Heidegger's philosophy. Furthermore, philosophical hermeneutics should resist, with equal caution of self-criticism, in stimulating too much of this counterpart reflective validity in order to challenge the arrogant place able to propel the verdict of the final word or the last intransitively foundation considered as an ultimate point of view, behold the assumption of its universality stands on the critical path of the metaphysical finitude, that is, on the horizon of a program stripped of absolute or totalitarian overtones.